Characterization of the ante-mortem transportation, capture chase and waiting time of indigenous chicken reared under traditional system in Benin. - BONOU, ASSOUAN GABRIEL; AHOUNOU, GBÊNAGNON SERGE; SALIFOU, CHAKIRATH FOLAKÊ ARIKÊ; Fanou, Arnaud Yetonde; SEIBOU TOLEBA, SOUMANOU; KONSAKA, BERNADETTE M.; DAHOUDA, MOHAMADOU; DOUGNON, TOSSOU JACQUES; FAROUGOU, SOUAÏBOU (My University, 2017)
Understand animal pre-slaughter conditions, is very important to prevent stress and its subsequent detrimental effects on meat quality. The current study aims to clear up the ante-mortem transportation, capture chase and waiting time conditions of local chicken. A survey was carried out on 50 poultry traders or sellers and 50 breeders in the townships of Abomey-Calavi, Allada, Zè, Toffo and Ouidah. Data on the process of these factors and on birds handling were collected. The survey revealed that from a township to the other, conditions are almost similar. Chickens were transported mainly in the morning by car, motorcycle and bicycle or simply by tradesmen walking on a distance of 7.10 to 59.72 km during 33 to 169 minutes. During the transportation, they were put in cages, in baskets or simply attached in clusters and hung up to a support. The two legs of each bird were tied together and they were feed and watered before the transportation or on arrival by some. Cases of accident, disease and mortality occurred. The capture chase took place every time outdoor or in a fence in Abomey-Calavi and outdoor, in a fence or in a house in the other localities and involved 1 to 3 persons. It lasted 8 to 19.1 minutes. Chickens caught were immediately slaughtered or put in cages or under baskets before. During the waiting time, feed withdrawal is not observed. Globally, the ante-mortem conditions of local chicken in these localities didn’t respect animal welfare and could produce stress.
Keywords: Chicken welfare; Transportation; Capture chase; Feed withdrawal; Benin